2006
DOI: 10.1016/s0001-2092(06)63968-9
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the OR for Baccalaureate Nursing Students

Abstract: Students in baccalaureate nursing programs often receive minimal exposure to specialty areas such as perioperative nursing, and new nurses may therefore fail to consider perioperative nursing as a potential practice area. Instructors from one college of nursing partnered with local hospitals to develop a program to introduce baccalaureate nursing students to the perioperative nursing specialty. This partnership program had positive outcomes for the college, the health care facilities, and the students. Six nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Previous reports addressing the experiences of nursing students in the OR demonstrate a positive correlation in choice of specialty upon graduation similar to those reported for medical students [13]. However, it was interesting to find that the three groups surveyed did not demonstrate parity in rating the importance of OR observation for nursing students with that of medical students.…”
Section: Discussionmentioning
confidence: 56%
“…Previous reports addressing the experiences of nursing students in the OR demonstrate a positive correlation in choice of specialty upon graduation similar to those reported for medical students [13]. However, it was interesting to find that the three groups surveyed did not demonstrate parity in rating the importance of OR observation for nursing students with that of medical students.…”
Section: Discussionmentioning
confidence: 56%
“…An initial version of our programme was first developed in 2010, centred around a curriculum that was designed to address some of the common educational needs of preclinical medical and nursing students that have been identified in the literature and emphasized in similar programmes [2,5,7,9,10], as well as to address the technical skills that are pertinent to the clinical encounters expected of clinical clerks at our institution [35].…”
Section: Course Development and Implementationmentioning
confidence: 99%
“…However, there appears to be considerable student interest in receiving early hands-on exposure to these disciplines [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some schools off er a very superfi cial content in the surgical nursing discipline and the prac cal part consists of visi ng OR units. This quick exposure to the OR or an internship that is limited to a few days of observa on implies that students will not be able to become involved in ac vi es in the periopera ve environment or iden fy what the nurses' role is in the OR unit (14) .…”
Section: Repercussions Of Ncd In Opera Ng Room Teachingmentioning
confidence: 99%
“…Due to the high demand for professionals in the labor market in the United States, health care services have hired nurses without a specializa on degree in the area, and, therefore, ins tu ons deal with unprepared professionals who, for this reason, are also incapable of keeping the job (14) . An evalua on regarding newly graduated nurses observed that without the opportunity to gain experience on context-based skills, graduates have reported a feeling of not feeling prepared (17) .…”
Section: Repercussions Of Ncd In Opera Ng Room Teachingmentioning
confidence: 99%